Parent Satisfaction : Contribution of Parental Involvement and School Service Quality Perception at Public Elementary School - Anindya Savira; Ujang Sumarwan; Istiqlaliyah Muflikhati (Jurnal Paedagogy, 2024)
This study aims to identify the characteristics, parental involvement, school service quality, and parent satisfaction of public elementary school students and analyze the influence of parental involvement and school service quality on parent satisfaction of public elementary school students. This research used a quantitative approach with a survey method, using cluster random sampling, and a questionnaire was distributed to 119 parents whose children are at the elementary school level in Bekasi City. The data was collected and then processed with descriptive tests and impact tests using SPSS and SmartPLS. The results showed that parental involvement did not have a direct impact on parent satisfaction, but it was moderated by school service quality. School service quality perception had a direct and significant impact on parent satisfaction. Parents need to be more aware of the role they play in their children's education and make an effort to be involved in children's learning process. For schools, it is necessary to periodically evaluate the quality of school services because it greatly influences parental satisfaction.